Assessing Monetary Policy in Norway - Harald Magnus Andreassen; Paul De Grauwe; Haakon Solheim; Øystein Thøgersen (Center for Economic Studies and ifo Institute (CESifo), 2001)
We evaluate the policy of flexible inflation targeting implemented by the Norges Bank since March 2001. We discuss the reasons why the real interest rates are significantly higher in Norway than in the rest of Europe. Finally we propose some institutional changes that can improve the policy making process.
Keywords: 330